PROGNOSTIC SIGNIFICANCE OF ECHOCARDIOGRAPHIC INDICATORS IN NEWBORNS WITH EXTREME LOW BODY WEIGHT AND PATENT DUCTUUS ARTERIUS - Пересторонина, Мария Вячеславовна; Москавчук, Станислав Владимирович; Корпачева, Ольга Валентиновна; Торопов, Андрей Петрович (Medicine in Kuzbass, 2024)
In recent years, there has been a significant increase in the role of echocardiographic examination in the diagnosis of pathology of the cardiovascular system in newborns, in particular, patent ductus arteriosus (PDA) in newborns with extremely low body weight. It can be assumed that there is a prognostic significance of EchoCG indicators for the long-term functioning and hemodynamic significance PDA. The aim of the research – to study the prognostic value of EchoCG parameters in newborns with extremely low body weight (ELBW) in the assessment of long-term persistent haemodynamically significant patent ductus arteriosus (hsPDA). Materials and methods. In a retrospective study, 2 groups were formed according to the data of echocardiographic cardiac evaluation: 1st – newborns in whom the arterial duct was closed (n = 25), in the 2nd – prolonged persistence of hsPDA was noted (n = 15). The association of echocardiographic parameters with long persistence of hsPDA was analysed using Spearman correlation and logistic regression method (Backward Stepwise, Wald), as well as ROC-analysis. Within the 2nd group, a dynamic comparison of the main echocardiographic parameters (ECG-parameters) of hsPDA was performed by periods of life (1-2 and 3-4 weeks). Comparison of two related groups was performed by the «sign criterion» method. Results. A strong statistically reliable association of hsPDA with the following ECG-parameters was established: left atrial size (LA), ratio of LA size to aortic root (LA/Ao), left ventricular end diastolic diameter (LVEDD), left ventricular end systolic diameter (LVESD), interventricular septum thickness. According to ROC analysis: LA size has greater sensitivity and specificity for predicting hsPDA than the LA/Ao index. Two prognostic formulas with maximum sensitivity (96 %) and specificity (80 %) were generated by logistic regression method: The 1st one includes LA size and interventricular septum thickness, the 2nd one includes LA/Ao, interventricular septum thickness and Ao size. In the group of newborns with hsPDA showed a significant increase in LA size and thickening of the posterior wall of the left ventricle by 3-4 weeks of life. Conclusion. A number of ECG-parameters have significant prognostic value for the assessment of hsPDA in ELBW neonates in the first week of life. Ethics. The study was approved by the Local Ethical Committee of Omsk State Medical University, protocol N 6 dated 11.05.2023.